2014
DOI: 10.1016/j.ejvs.2014.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Graft Durability and Fatigue after In Situ Fenestration of Endovascular Stent Grafts Using Radiofrequency Puncture and Balloon Dilatation

Abstract: While the Zenith fabric was the strongest both before and after fenestration, it requires further study with cutting balloons to achieve full-sized fenestrations. All fenestrations remained stable during fatigue testing except for the Talent fabric. This study serves as the baseline for future studies that will include stent grafts, branch stents, and cutting balloons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 14 publications
1
30
0
1
Order By: Relevance
“…Bench testing has shown that ePTFE stent grafts require higher RF energy for fenestration compared with what is needed for Dacron stent grafts. 11 In addition, embolization has also been described after RF use for cardiac ablation. 15,16 Theoretically, laser generated fenestrations have several advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Bench testing has shown that ePTFE stent grafts require higher RF energy for fenestration compared with what is needed for Dacron stent grafts. 11 In addition, embolization has also been described after RF use for cardiac ablation. 15,16 Theoretically, laser generated fenestrations have several advantages.…”
Section: Discussionmentioning
confidence: 99%
“…This practice is based on our bench studies, 11 as well as those of Riga et al, 9 in which satisfactory fenestration diameters could not be achieved with conventional balloons on Zenith stent-grafts. We have not yet tried high-pressure balloons for fenestration, but this would certainly be an alternative to cutting balloons.…”
Section: Discussionmentioning
confidence: 98%
“…Other ablation systems include radiofrequency (RF) Guidewire. However the energy associated with the RF Guidewire is unsuitable for polymer ablation because it mainly causes melting, burning, and deterioration of the prosthesis material .…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of in situ laser fenestration of thoracic devices has been previously highlighted by our team and other centers as well, that is, Manning , McWilliams , Murphy , Sonesson , Riga to name a few. Cutting balloons have been considered but this requires a laser perforation of the fabric as a first step in the fenestration procedure (18) and might represent a sound approach in the case of urgent treatment . The possibility of fenestrating devices in the operating room by means of ophthalmic cauterization has also been proposed, but it requires deployment and reloading of the endograft, which proved to be difficult with devices which have barbs and/or hooks .…”
mentioning
confidence: 99%